COVID-19 and the cardiovascular system in pregnancy - Herrey, AS; Osman, A; Soma-Pillay, P; Sliwa, K; Ntusi, NAB (SA Heart Journal, 2020)
Pregnancy and coronavirus disease-2019 (COVID-19) share several common features which makes differentiation between the 2 difficult. Both are multisystem disorders, may present with breathlessness, are associated with hypercoagulability and frequently cause significant anxiety in both the patient and those around them. Pregnancy represents a state of partial immune suppression, with pregnant women more vulnerable to viral infections. However, these concerns have not been borne out in clinical practice and have not stood up to epidemiological scrutiny. From limited data available on COVID-19 in pregnancy, the outcomes are mostly favourable. While cardiac disease and hypertension are independent predictors of hospital admission with COVID-19 in pregnancy, the prevalence of cardiac disease in the pregnant COVID-19 population is low. Pregnant women are younger, and asymptomatic SARSCoV-2 infection and favourable outcomes are reported in those below 55 years of age. Indeed, large numbers of asymptomatic cases have been reported in pregnancy, suggesting that pregnant patients with more severe disease courses may be over-represented in the current literature, particularly the early case reports and case series. Cardiovascular involvement in pregnancy includes new-onset hypertension, myocarditis, cardiomyopathy, pulmonary embolism and a pre-eclampsia-like syndrome.